2019
DOI: 10.1088/1367-2630/ab0119
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of radiation friction losses in laser-driven ‘hole boring’ of dense targets

Abstract: In the interaction of laser pulses of extreme intensity (>10 23 Wcm −2 ) with high-density, thick plasma targets, simulations show significant radiation friction losses, in contrast to thin targets for which such losses are negligible. We present an analytical calculation, based on classical radiation friction modeling, of the conversion efficiency of the laser energy into incoherent radiation in the case when a circularly polarized pulse interacts with a thick plasma slab of overcritical initial density. By a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…( 11) considerably deviates from its low-field, a 0 a cr , a HB , and the high-field a 0 a cr , a HB asymptotics. For the supergaussian pulse F (ρ, τ ) = exp(−ρ 2 − τ 4 ) as used in [25,26] the low-field asymptotic of η rad , Eq. ( 19), is given by…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 11) considerably deviates from its low-field, a 0 a cr , a HB , and the high-field a 0 a cr , a HB asymptotics. For the supergaussian pulse F (ρ, τ ) = exp(−ρ 2 − τ 4 ) as used in [25,26] the low-field asymptotic of η rad , Eq. ( 19), is given by…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Eq. ( 16) in [26]. This equation relates to the case of a laser field homogeneous both in the propagation direction and the polarization plane.…”
Section: Quantum Effect On the Conversion Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The relativistic transparency and hole-boring regimes are found to be sensitive to the transverse plasma field, backward light reflection, and laser pulse filamentation. Popruzhenko et al (2019) have shown that in the interaction of laser pulses of extreme intensity ( [ 10 23 W cm À2 ) with high-density and thick plasma targets, significant radiation friction losses in simulations, in contrast to thin targets for which such losses are negligible. They have presented an analytical calculation,…”
Section: Pic Simulations Of Laser-plasmas Physicsmentioning
confidence: 99%
“…A white curve on the upper panel shows the radiation power integrated over x. Image reproduced from Popruzhenko et al (2019), copyright by the authors report estimates of self-heating rates, convergence of collisional routines and test of ionisation models which are not readily available elsewhere. Having reviewed the status of PIC algorithms they have presented a summary of recent applications of such codes in laser-plasma physics, concentrating on stimulated Raman scattering, short-pulse laser-solid interactions, fast-electron transport, and QED effects.…”
Section: Pic Simulations Of Laser-plasmas Physicsmentioning
confidence: 99%